PENGEMBANGAN PERANGKAT LUNAK KOMPUTER UNTUK MENGEVALUASI SOAL TES - Hindayati Mustafidah (Universitas Sebelas Maret, 2009)
This research aims to develop computer software used to evaluate some test itemssuchascalculationanddeterminationforvalidity,reliability,differencepower,and difficulty indexes. This software is developed using C++ programming language. This computer software is called “evaluasi”. An algorithm is designed before making a thinking runs easily at the program making. This software consists of two menus that can bechosenforthekindoftestitems.Twomenusarefordataentryforstudent'stestscores, and four menus are for evaluating the kind of test items. The kinds of items consist of a multiple choice test and an essay test. There are two ways for inputting data, from the keyboard or from the data which were saved in file. This system prepares four types of evaluation that can be selected by user. They are validity, reliability, difference power, anddifficultyindexes;eachtypeofthemisformultiplechoiceitemandessayitem.